Strategy Formulation of Business Development in Catfish Hatchery Aquaculture (Study on The Panca Wargi Fish Group in Kecamatan Pacet Bandung Regency) - Muhamad Rizki Pratama; Fanji Wijaya; Ezra Karamang (Dinasti International Journal of Education Management And Social Science, 2024)
The research was conducted with the aim of finding innovations in designing business development strategies oriented to the external and internal conditions of the Panca Wargi Group. The approach chosen is a qualitative methodology that utilises primary and secondary data types in obtaining information. Interviews were conducted with fourteen interviewees, namely the group leader, core management, and group members. In this strategy planning, the IFE Matrix and EFE Matrix have outlined the internal and external aspects of the group as a basis for strategy design. Based on the results of the Internal and External Matrix (IE), it is found that the condition of the group is in position V which leans towards market penetration and product development strategies with the aim of maintaining stable business growth. The V position of the panca wargi fish group indicates that the internal and external aspects have almost equal strength, which in the losng run will lead to stagnant business development, which may turn out to be dangerous in the future. With the use of the TOWS Matrix and QSPM Matrix, the twelve best alternative strategies have been compiled based on the TAS value to optimise the use of strategies. Panca Wargi Fish Group can get the best business development results starting from having the right strategy formulation.